A condicionalidade de educação no Programa Bolsa Família: reflexões sobre os requisitos de inclusão e permanência - Lima, Lucimar Pereira (2021)
This article aims to analyze the conditionality of education and the requirements for inclusion and permanence in the Bolsa Família Program, based on reflections on a set of categories, such as: enrollment, school attendance and differentiated attendance in rural education. To achieve this goal, a bibliographical study was carried out to understand the laws and regulations about the conditionality of education of the program, scientific discussions were identified and the categories of educational conditioning factors such as enrollment, school attendance and differentiated attendance in rural education were evaluated. In this sense, it is possible to consider that the Bolsa Família Program is one of the most important social protection actions, however, social inequalities are one of the great challenges in Brazilian society. To overcome it, we need policies and programs that guarantee social rights and the full exercise of citizenship.